2001
DOI: 10.1046/j.1365-3180.2001.00232.x
|View full text |Cite
|
Sign up to set email alerts
|

Ranking the ability of wheat varieties to compete with Lolium rigidum

Abstract: The relative competitive advantage of 12 commercially available wheat varieties was examined against Lolium rigidum Gaud. at a number of sites from 1995 to 1997 in south‐eastern Australia. Nearly all the variation in crop grain yield was attributable to the variety × environment effects (81%), with only 4% due to variety × weed × environment effects. Some varieties exhibited an environment‐specific competitive advantage, for example Katunga, Dollarbird and Hartog, whereas others like Shrike, Rosella and Janz w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
101
1
9

Year Published

2004
2004
2017
2017

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 118 publications
(116 citation statements)
references
References 19 publications
5
101
1
9
Order By: Relevance
“…The list contains cultivars of common leguminous, graminaceous and brassica crop species, and species such as rye (Batish et al 2001;Fujii 2001;Bhowmik and Inderjit 2003;Singh et al 2003) and nearly 80 tree species (Rizvi et al 1999). Lemerle et al (2001) studied the effects of several wheat varieties on perennial ryegrass (Lolium perenne) and found that negative effects on the weed were partly due to environmental conditions but also due to genotype, and individual weed inhibiting traits. The structure of weed communities is also altered by intercropping.…”
Section: Weed Suppression Via Belowground Mechanismsallelopathymentioning
confidence: 99%
“…The list contains cultivars of common leguminous, graminaceous and brassica crop species, and species such as rye (Batish et al 2001;Fujii 2001;Bhowmik and Inderjit 2003;Singh et al 2003) and nearly 80 tree species (Rizvi et al 1999). Lemerle et al (2001) studied the effects of several wheat varieties on perennial ryegrass (Lolium perenne) and found that negative effects on the weed were partly due to environmental conditions but also due to genotype, and individual weed inhibiting traits. The structure of weed communities is also altered by intercropping.…”
Section: Weed Suppression Via Belowground Mechanismsallelopathymentioning
confidence: 99%
“…For producers, knowledge about the competitive ability of varieties would be useful for choosing varieties suited to their environment (Lemerle et al 2001b). Yield gains of 7-9% have been identified in "competitive" wheat varieties when compared with "noncompetitive" varieties (Hucl 1998).…”
Section: Genetic Variation For Competitive Ability In Wheatmentioning
confidence: 99%
“…A better understanding of such mechanisms, morphological and physiological, would not only serve to assist plant breeders in developing competitive varieties more quickly and effectively, but would also justify the use of plant breeding to increase crop competitive ability (Lemerle et al 2001b).…”
Section: Breeding For Competitive Abilitymentioning
confidence: 99%
“…Wheat crop tolerance (yield) and weed suppression were broadly correlated in several studies (Challaiah et al 1986;Lemerle et al 1996), although other results (Coleman et al 2001;Lemerle et al 2001) found no wheat genotype that had consistently high tolerance and a high level of weed suppression. The studies by Siddique and Belford (1989) have shown a negative correlation between grain yield potential and the morphological characteristics that provide high competitive ability.…”
Section: Discussionmentioning
confidence: 85%
“…The competitive ability of wheat could be improved by choosing from available varieties or by breeding for competitiveness. It was reported that taller older varieties were more tolerant against weeds by maintaining a yield level in weedy environments (Cosser et al 1997;Lemerle et al 2001;Didon 2002;Bertholdsson 2005).…”
Section: Introductionmentioning
confidence: 99%